2000
DOI: 10.1002/1097-0088(20000615)20:7<759::aid-joc494>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Statistical relationships between solar UVB and UVA radiation and global radiation measurements at two sites in Israel

Abstract: Statistical relationships between the hourly radiation intensity values of both ultraviolet-B (UVB) and ultraviolet-A (UVA), and of the corresponding global radiation at two sites in Israel, the Dead Sea and Beer Sheva, are presented using radiation data measured from January 1995 to January 1999. It was determined, based upon the square of the correlation coefficient (r 2 ), that in the case of the UVB, a quadratic equation provided a better fit of the database, whereas in the case of UVA, a linear equation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 11 publications
5
20
0
Order By: Relevance
“…1 and 2a, b represents an almost vanishing j (NO 2 )↓ increase at small SZAs, while G is still benefiting from the increase of the cosine weighting factor. Correlating j (NO 2 ) with the UV irradiance also results in a curvature with increasingly higher values of the UV irradiance (Madronich, 1987a) and consistently, the relationship between UV-A irradiance and G can be described by a near-linear dependency (Canada et al, 2003;Jacovides et al, 2006;Kudish and Evseev, 2000;Ogunjobi and Kim, 2004). However, some previous studies also found near-linear relationships between j (NO 2 ) and G (e.g., Bahe et al, 1980;Brauers and Hofzumahaus, 1992;Schere and Demerjian, 1978;Wratt et al, 1992).…”
Section: Resultsmentioning
confidence: 71%
“…1 and 2a, b represents an almost vanishing j (NO 2 )↓ increase at small SZAs, while G is still benefiting from the increase of the cosine weighting factor. Correlating j (NO 2 ) with the UV irradiance also results in a curvature with increasingly higher values of the UV irradiance (Madronich, 1987a) and consistently, the relationship between UV-A irradiance and G can be described by a near-linear dependency (Canada et al, 2003;Jacovides et al, 2006;Kudish and Evseev, 2000;Ogunjobi and Kim, 2004). However, some previous studies also found near-linear relationships between j (NO 2 ) and G (e.g., Bahe et al, 1980;Brauers and Hofzumahaus, 1992;Schere and Demerjian, 1978;Wratt et al, 1992).…”
Section: Resultsmentioning
confidence: 71%
“…Several authors have presented models for estimating the UVB irradiance from data on UVA or global irradiance. Kudish and Evseenv (2000) show a statistical 699 relationships between the UVB and UVA irradiances and the global irradiance at two sites in Israel. They indicate that the calculation of the UVA irradiance from the global irradiance behaves better than the calculation of the UVB irradiance from the Global because of the dominant role that ozone plays in the attenuation of the UVB and its practically negligible effect on the attenuation of the UVA and global irradiances.…”
Section: Resultsmentioning
confidence: 99%
“…Koronakis et al [22] reported an annual mean value of 4.1% over polluted Athens, Greece, whereas Kudish and Evseev [23], using UV-A measurements, found percent ratio values varying between 4.35% and 5.19% in the Dead Sea basin, Israel. However, the reported range of correlations suggests the desirability of local calibration to account for specific climatic conditions.…”
Section: Introductionmentioning
confidence: 98%